Unified Modeling Language (UML) Model Untuk Pengembangan Sistem Informasi Akademik Berbasis Web - M Teguh Prihandoyo (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Information technology are two things that can not be separated at this time, it is seen from the process to obtain information that can be obtained quickly, precisely, and accurately supported by technological progress is increasingly sophisticated. Politeknik Harapan Bersama Tegal is one of the educational institutions that have a complete system in data processing, which requires all data to be well processed, stored neatly and easily traced. The purpose of this research is to develop academic information system at Politiknik Harapan Bersama Tegal by using Unified Modeling Language (UML) model as model development that made. The final result of this research is a web-based acadeic information system that can provide optimization of Service Plan study cards and students of Politeknik Harapan Bersama Tegal.